Understanding Jump Landing as an Oscillating System: A Model-based Approach of Balance and Strength Analyses - Hellmers, Sandra; Fudickar, Sebastian; Dasenbrock, Lena; Heinks, Andrea; Bauer, Jürgen M; Hein, Andreas (Proceedings of the 10th International Joint Conference on Biomedical Engineering Systems and Technologies, 2017)
Counter movement jumps (CMJ) are well-suited to measure the muscle power and balance. Since it has been clarified that well accepted CMJ amplification-based balance measures (such as TTS or CoP) are significantly influenced by algorithmic and measurement settings and thus, measurement results have limited meaningfulness among force platforms, we introduce a new model-based approach measuring the postural stability. In this, during the landing and recovery phases after vertical jumps, the lower extremities can be represented by an oscillating system and the corresponding transfer function is described by a second-order delay (PT2) element. In an initial prospective study with 20 subjects aged over 70 years, we observed an inverse relationship between the natural frequency and the jump height and could also identify an influence of sex, and body weight on the jump height. Furthermore, we also found a strong relation between natural frequency and dynamic postural stability index (DPSI), even though these results must be statistically ensured statistically using a larger cohort, due to the current limited number of subjects. Nevertheless, we could confirm the general applicability of the Systems and Control Technology perspective on describing human movements in a potentially more robust manner than current amplification based approaches.